The Bourne legacy [videorecording (Blu-Ray + DVD)] - Renner, Jeremy; Norton, Edward; Glenn, Scott, 1942-; Weisz, Rachel, 1970-; Murphy, Donna; Ludlum, Robert, 1927-2001; Gilroy, Tony; Gilroy, Tony; Gilroy, Dan, 1959- (Ludlum, Robert. Jason Bourne, 2012)
Aaron Cross is an agent groomed by the government program that also unleashed Jason Bourne, but with a few new wrinkles. Cross is busy training in Alaska when he's caught in a tsunami of hurt, thus beginning a frantic search for answers to who and what he is.